Introducing NMR strategies to define water molecules that drive metal binding in a transcriptional regulator - M. Villarruel Dujovne; M. Bringas; I.C. Felli; E. Ravera; S. Di Lella; D.A. Capdevila (Journal of Magnetic Resonance Open, 2023)
Staphylococcus aureus CzrA is a paradigmatic member of the ArsR family of transcriptional metalloregulators, which are critical for the bacterial response to stress. Zinc binding to CzrA, which induces DNA derepression, is entropically driven, as shown by calorimetry. A detailed equilibrium dynamics study of different allosteric states of CzrA revealed that zinc induces an entropy redistribution that controls for DNA binding regulation; however, this change in conformational entropy only accounts for a small net contribution to the total entropy. This difference between the change in conformational entropy vs. total entropy of zinc binding implies a significant contribution of solvent molecule rearrangements to this equilibrium. However, the absence of major structural changes suggests that solvent rearrangements occur mainly on the protein surface and/or from zinc desolvation, concomitant with a dynamical redistribution of conformational entropy. Previous results also suggest that zinc binding not only leads to a redistribution of protein internal dynamics, but also release of water molecules from the protein surface. In turn, these water molecules may make a significant contribution to the allosteric response that results in dissociation from the DNA.Quantifying the differential hydration of two conformational states that share very similar crystal structures and then correlating this with the protein's solvent entropy change constitutes an unresolved problem, even when thermodynamics suggest a significant contribution of solvent entropy. Here, we present different avenues to dissect hydration dynamics in a metal-binding transcriptional regulator that provide different insights into this complex problem. We explore primary solution NMR tools for probing protein–water interactions: the laboratory frame nuclear Overhauser effect (NOE) and its rotating frame counterpart (ROE) between long-lived water molecules and the protein residues. The wNOE/wROE ratio is a promising tool for the detection of hydration dynamics near the surface of a protein in a site-specific manner, minimizing contamination from bulk solvent. Molecular dynamics simulations and computational methods designed to provide a spatially resolved picture of solvent thermodynamics were also employed to provide a more complete panorama of solvent redistribution.